Uma avaliação fisiopatológica da participação de células leucocitárias na malária experimental - Flores, Carlos Alberto (1983)
The present work demonstrated that Swiss-44 or B 10A mice developed, during the P.berghei-malaria, a drastic pulmonary edema, hypothermia and leucocyto- sis (with neutrophilia and lymphocytosis). A close relationship between leucocytosis and pulmonary and body temperature changes were observed. The treatment of infected animais (Swiss-44 or B 10A) with methotrexate (MTX) caused a strong inhibition of the pathologic alterations observed. Swiss-44 mice treated with MTX or infected with P.berghei and infected with the parasite and treated with MTX presented no alterations on total plasma protein leveis, during the seven days of study. The administration of mononuclear splenic cells (CME) from normal isogenic mice to infected and MTX treated B 10A mice was ineffective in producing a reversal of the inhibited phenomena. However, normal mice that received transference of CME from infected animais (7th. day of infection) showed a discret rise in the Lung wet weight/Body weight ratio, that was ma- ximal at 3rd. hour after the transference. This alte- ration was paralelled by neutrophils countings, although no relationship between total leucocytes or lymphocytes counts could be established. These results showed evidences that blood white cells, possibly neutrophils and/or lymphocytes, could participate directly and/or indirectly in pulmo- nary edema and hypothermia observed in P.berghei-mala- ria.